YHWH is there: Ezekiel's temple vision as a type - Grumbles, Drew N. (Wipf and Stock, 2021)
How do we make sense of Ezekiel 40-48? Ezekiel's temple vision has long mystified Bible readers and scholars. Is this a temple that is going to be built in the future? Or is this merely symbolic? Why so many details? Is there any relevance to this section of the Old Testament at all? This book addresses these important questions, showing how Ezekiel's temple is more than just symbolic. Yet its ultimate fulfillment is not in any physical building, but, according to the New Testament, in Jesus and the new heavens and new earth. Not only will this book illuminate Ezekiel 40-48 for you, it will also help you understand important issues of interpretation in our day, such as typology, the role of the temple in biblical theology, and the New Testament use of the Old Testament. You will learn that yes, in fact, Ezekiel 40-48 is very relevant to the Bible's storyline